How the Topology of the Mitochondrial Inner Membrane Modulates ATP Production - Raquel Adams; Nasrin Afzal; Mohsin Saleet Jafri; Carmen A. Mannella (Cells)
Cells in heart muscle need to generate ATP at or near peak capacity to meet their energy demands. Over 90% of this ATP comes from mitochondria, strategically located near myofibrils and densely packed with cristae to concentrate ATP generation per unit volume. However, a consequence of dense inner membrane (IM) packing is that restricted metabolite diffusion inside mitochondria may limit ATP production. Under physiological conditions, the flux of ATP synthase is set by ADP levels in the matrix, which in turn depends on diffusion-dependent concentration of ADP inside cristae. Computer simulations show how ADP diffusion and consequently rates of ATP synthesis are modulated by IM topology, in particular (i) number, size, and positioning of crista junctions that connect cristae to the IM boundary region, and (ii) branching of cristae. Predictions are compared with the actual IM topology of a cardiomyocyte mitochondrion in which cristae vary systematically in length and morphology. The analysis indicates that this IM topology decreases but does not eliminate the “diffusion penalty” on ATP output. It is proposed that IM topology normally attenuates mitochondrial ATP output under conditions of low workload and can be regulated by the cell to better match ATP supply to demand.